2017
DOI: 10.12788/jhm.2875
|View full text |Cite
|
Sign up to set email alerts
|

Interhospital Transfer and Receipt of Specialty Procedures

Abstract: The practice of transferring patients between acute care hospitals is variable and largely nonstandardized. Although often-cited reasons for transfer include providing patients access to specialty services only available at the receiving institution, little is known about whether and when patients receive such specialty care during the transfer continuum. We performed a retrospective analysis using 2013 100% Master Beneficiary Summary and Inpatient claims files from Centers for Medicare and Medicaid Services. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 10 publications
3
25
0
Order By: Relevance
“…12,24 This indicates our patients were in much less critical conditions than those in other studies. Finally, similar to findings from other studies 7,8 , the patients' profiles of our study were heterogeneous (Table 2).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…12,24 This indicates our patients were in much less critical conditions than those in other studies. Finally, similar to findings from other studies 7,8 , the patients' profiles of our study were heterogeneous (Table 2).…”
Section: Discussionsupporting
confidence: 89%
“…2 Additional to the systemic threats, growing evidence demonstrated higher acute severity, a longer length of stay, higher hospital mortality and higher resources use in IHT patients when compared to non-IHT cases. [3][4][5][6][7] These undesirable outcomes of IHT patients could be due to heterogeneity among IHT patients depending on the diagnosis, presenting a nuanced assessment of this complex care transition. 8 Variability in transfer practices means ambiguity and subjectivity in decision making between transferring physicians and receiving physicians.…”
Section: Introductionmentioning
confidence: 99%
“…Several published studies support an association between IHT and higher mortality [1,2,20,21]. Contrarily, in the present study, we found that IHT patients had fewer complications as measured by CDS.…”
Section: Pertinent Negatives: Decreased Cds In Ihtsupporting
confidence: 88%
“…In a retrospective study of IHT in patients with acute myocardial infarction, Mueller et al [ 23 ] pointed out that medical transfer often occurred in the hospital, which made patients face the potential risk of nursing interruption. Thus, patients and medical staff experienced some pressure.…”
Section: Discussionmentioning
confidence: 99%